Koneksitas Linier Musik Terhadap Pertunjukan Tari Tradisi - Maryono Maryono (Institut Seni Indonesia Surakarta, 2012)
The linear interconnection of traditional music toward tradition dance performance has important role as accompanied music with vital contribution. Traditional music called karawitanÂ in a dance performance not only has function as accompanied music but also being: (1) guidance for content or meaning; (2) integrated (nyawiji); (3) rested (nglambari); and (4) wrapped (mungkus) in a whole dance and therefore represented a quality art performance. The interconnection of traditionalÂ music toward tradition dance performance was a fusion feel that integrated in expression quality. Keywords : interconnection, traditional music called karawitan, and tradition dance performance.Â